2016
DOI: 10.1002/hep.28774
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling regulates hepatobiliary repair following cholestatic liver injury in mice

Abstract: Hepatic repair is directed chiefly by the proliferation of resident mature epithelial cells. Further if predominant injury is to cholangiocytes, the hepatocytes can transdifferentiate to cholangiocytes to assist in the repair and vice versa as shown by various fate-tracing studies. However, the molecular bases of reprograming remain elusive. Using two models of biliary injury where repair occurs via cholangiocyte proliferation and hepatocyte transdifferentiation to cholangiocytes, we identify an important role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(115 citation statements)
references
References 39 publications
(94 reference statements)
6
109
0
Order By: Relevance
“…To confirm if β‐catenin is regulating these two targets spatiotemporally, we next used liver cryosections from baseline control mice, control mice after 12 hours PH, and β‐catenin‐LKO after 12 hours PH. The sections were microdissected, and pooled scrapings from the periportal zone, pericentral zone, and midzone were used for messenger RNA (mRNA) isolation and reverse‐transcription qPCR, as described in the Material and Methods and previously20 (http://onlinelibrary.wiley.com/doi/10.1002/hep4.1196/full). The relative purity of various zones was verified by analysis of genes with known zonal expression (http://onlinelibrary.wiley.com/doi/10.1002/hep4.1196/full).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm if β‐catenin is regulating these two targets spatiotemporally, we next used liver cryosections from baseline control mice, control mice after 12 hours PH, and β‐catenin‐LKO after 12 hours PH. The sections were microdissected, and pooled scrapings from the periportal zone, pericentral zone, and midzone were used for messenger RNA (mRNA) isolation and reverse‐transcription qPCR, as described in the Material and Methods and previously20 (http://onlinelibrary.wiley.com/doi/10.1002/hep4.1196/full). The relative purity of various zones was verified by analysis of genes with known zonal expression (http://onlinelibrary.wiley.com/doi/10.1002/hep4.1196/full).…”
Section: Resultsmentioning
confidence: 99%
“…We cut 10‐μm sections on a microtome and stained these with hematoxylin and eosin. For microdissection, specific areas were scraped manually under the microscope and materials from specific zones were pooled together from multiple areas and slides as described 19, 20. RNA was extracted as described below.…”
Section: Methodsmentioning
confidence: 99%
“…These transgenic mice exhibited a dramatic increase in the numbers of A6-positive hepatocytes, which constituted almost the entire hepatic lobule as compared to controls, which showed only limited and localized periportal presence of A6-positive hepatocytes. A more recent study showed that this transdifferentiation corresponded with increased YAP signaling (161). This study further strengthened the role of Wnt signaling in hepatobiliary repair, as mice fed a DDC diet exhibited a significant upregulation of Wnt7a, which induced Sox9 expression and increased β-catenin reporter activity in cultured hepatocytes.…”
Section: Cell Type–specific Roles Of Wnt/β-catenin Signaling In Livermentioning
confidence: 98%
“…DDC-diet-fed mice with liver-specific deletion of Wntless, which prevents Wnt secretion from hepatocytes and BECs, displayed reduced BEC proliferation and abrogated hepatocyte–BEC transdifferentiation. Finally, mice with liver-specific deletion of LRP5 and LRP6 subjected to BDL, another model of chiefly biliary injury, exhibited similar levels of BEC proliferation compared to wild-type littermates but lacked transdifferentiating hepatocytes (161). All these results suggest that BEC proliferation postbiliary injury is Wnt-dependent but β-catenin-independent, and Wnt/β-catenin signaling plays a role in promoting hepatocyte–BEC transdifferentiation.…”
Section: Cell Type–specific Roles Of Wnt/β-catenin Signaling In Livermentioning
confidence: 99%
“…3B), the presence of the single-positive cells suggest that the suppression of Wnt/β-catenin signaling represses Tp1:H2B-mCherry induction in hepatocytes, i.e., the formation of hybrid hepatocytes. This suggestion is supported by a recent mouse study showing that Wnt/β-catenin signaling induces the expression of biliary markers, such as Sox9, EpCAM and CK19, in hepatocytes 43 . Intriguingly, we found a similar phenotype in the MO-injected larvae upon macrophage ablation.…”
Section: Discussionmentioning
confidence: 58%